2019
DOI: 10.1002/ijop.12612
|View full text |Cite
|
Sign up to set email alerts
|

Applying self‐determination theory to understand the motivational impact of cash rewards: New evidence from lab experiments

Abstract: We investigated, based on self‐determination theory (SDT), the impact of the functional meaning of monetary rewards on individuals' motivation and performance and further tested the role of the psychological needs as the underlying mechanism. In two experimental studies, we show that when presented in an autonomy‐supportive way, rewards lead participants to experience greater intrinsic motivation, which leads them to perform better, than when monetary rewards are presented in a controlling way. This is mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…More precisely, our results are in line with prior research on compensation describing the impact of contingency cash rewards on employees’ motivation in organizations (e.g., see Thibault-Landry et al, 2017 ; Thibault-Landry et al, 2019b ; Olafsen and Deci, 2020 ). In this paper, using the Functional Meaning of Cash Rewards Scale, we demonstrated that using the monetary rewards perceived as informational led to healthier forms of motivation, greater psychological health, and better overall work intentions than did cash rewards perceived as controlling, because informational rewards are conducive to greater basic psychological need satisfaction.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…More precisely, our results are in line with prior research on compensation describing the impact of contingency cash rewards on employees’ motivation in organizations (e.g., see Thibault-Landry et al, 2017 ; Thibault-Landry et al, 2019b ; Olafsen and Deci, 2020 ). In this paper, using the Functional Meaning of Cash Rewards Scale, we demonstrated that using the monetary rewards perceived as informational led to healthier forms of motivation, greater psychological health, and better overall work intentions than did cash rewards perceived as controlling, because informational rewards are conducive to greater basic psychological need satisfaction.…”
Section: Discussionsupporting
confidence: 91%
“…Perhaps the most controversial set of the findings within the umbrella of SDT is directly related to pay—namely, the findings concerning reward effects on intrinsic motivation and related concepts. Even though contingency rewards have been initially represented as an antecedent of controlled motivation ( Gagné and Deci, 2005 ), prior research demonstrated that studying the motivational impacts of the reward itself is insufficient, it is rather the meaning (i.e., informative or controlling) associated with contingency rewards that could influence employees’ level of need satisfaction and work motivation (e.g., Thibault-Landry et al, 2019b ). Nevertheless, even though research on SDT should continue to investigate the contextual nature of rewards, the research did not find yet adequate validated tools to do so ( Forest et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thibault-Landry et al [ 70 , 73 ] have empirically argued that controlling monetary rewards have a negative psychological effect on employees, such as feeling pressured and coerced to behave in a certain way, leading to suboptimal functioning. In a Canadian context, other research by Thibault-Landry et al [ 74 ] highlighted the functional value of rewards beyond the reward itself, which can lead employees to focus on rewards and care little about the quality of work. In addition, rewards can generate hidden labor costs such as performing tasks dishonestly [ 75 ], completing tasks without the required standards [ 76 ], lowering the quality of services [ 77 ], or affecting job satisfaction or organizational performance [ 78 ].…”
Section: Literature Reviewmentioning
confidence: 99%